Lectotypification of Selaginella tenuissima and S. papagaiensis (Selaginellaceae) with the description of S. monticola - Valdespino, Ivan Alberto (Phytotaxa, 2015)
My revisionary work on the genus Selaginella demonstrates that many earlier species names are not properly typified. One of these concerns Selaginella tenuissima, an endemic species from Brazil, and its synonym S. papagaiensis. Therefore, I undertook a critical analysis of original material used to describe those species, along with pertinent literature. As a result, I propose a lectotypification of Selaginella tenuissima and of S. papagaiensis based on a Glaziou’s specimen at P and a Silveira’s gathering at R, respectively, and discuss the reasons for doing so. In addition, a new pseudo-criptic species, Selaginella monticola, is segregated from the previously broadly circumscribed S. tenuissima. Selaginella monticola is illustrated with scanning electron micrograph images of diagnostic characters that serve to separate it from S. tenuissima, which also allow its classification within subg. Stachygynandrum. Additionally, according to a preliminary assessment based on the Categories and Criteria of IUCN, I consider the conservation status of Selaginella monticola as of Least Concern (LC).